Myelomonocytic leukaemia (JMML) in a child with intellectual disability and chromosome 4q deletion - Harsha Prasada Lashkari; Naga Venkata Sirisha Andey; Nanda Kumar; Katta M. Girisha (Elsevier, 2021)
JMML is a rare aggressive type of leukaemia seen in children. It is often seen with syndromes such as Noonan, and neurofibromatosis type 1. Rarely it can be a sporadic event. The pathogenesis of myeloproliferation in this condition is due to the activation of the MAPK-RAS pathway. We here report an association of JMML having mutations in two known disease-causing genes PTPN11 and ASXL1 in a child with neurodevelopmental delay due to chromosome 4q deletion, for the first time.